TEACHING CHEMISTRY IN ENGLISH IN TURKISH UNIVERSITIES: CHALLENGES AND OBSTACLES - Tariq Elhadary; Ismail Elhaty (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2023)
No matter if they are in high school or college, Turkish students have particular challenges when trying to understand chemistry lectures delivered in English. The purpose of this study is to evaluate the difficulties Turkish students have when studying chemistry in English. A survey was administered to Turkish students at a Turkish University, nutrition and dietetics major in order to obtain relevant information. The results showed that 24.6% of students have difficulties learning chemistry in English, and 52.3% of the students are reluctant to give presentations in the chemistry class due to their lack of confidence in the English language. The results showed that the areas of weakness in the English language were conversational skills (78.5%), grammar (75.4%), vocabulary (75.4%), listening (72.2%), and reading (38.5%). Therefore, a considerable percentage of these students (48.6%) take their lecture notes in Turkish, and an overwhelming majority of them (46.2%) think that adding English terminology to textbooks alongside Turkish would help the problem. According to the research, it is possible to increase students' English skills and therefore their understanding of chemistry by employing various teaching strategies. To address communication hurdles in chemistry classes, the study heavily draws on both the Communicative and Natural Approaches.